2011
DOI: 10.1371/journal.pone.0016136
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Profiling of Tobacco Etch Virus Protease Using a Novel Fluorescence-Assisted Whole-Cell Assay

Abstract: Site-specific proteolysis of proteins plays an important role in many cellular functions and is often key to the virulence of infectious organisms. Efficient methods for characterization of proteases and their substrates will therefore help us understand these fundamental processes and thereby hopefully point towards new therapeutic strategies. Here, a novel whole-cell in vivo method was used to investigate the substrate preference of the sequence specific tobacco etch virus protease (TEVp). The assay, which u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…2D). The relative ranking of Cml-sensitivity correlated well to previously reported processing efficiencies of the three substrates [18,19]. Moreover, a previously described [17] inactive mutant (D81N) of TEVp together with the reporter containing a TEVp-specific substrate peptide (CAT-subG-ssrA) did not support cell growth (Fig.…”
Section: Bacterial Growth Is Linked To the Efficiency With Which Tevpsupporting
confidence: 86%
“…2D). The relative ranking of Cml-sensitivity correlated well to previously reported processing efficiencies of the three substrates [18,19]. Moreover, a previously described [17] inactive mutant (D81N) of TEVp together with the reporter containing a TEVp-specific substrate peptide (CAT-subG-ssrA) did not support cell growth (Fig.…”
Section: Bacterial Growth Is Linked To the Efficiency With Which Tevpsupporting
confidence: 86%
“…1A). An alternate form of the consensus cleavage site (ENLYFQ/G) (Kostallas et al, 2011) results in cleavage between the final glutamine and glycine, glycine being the first amino acid of MOG 1-125 . Therefore, TEV protease cleavage results in the removal of additional tag sequences, leaving pure MOG 1-125 extracellular domain without any residual amino acids.…”
Section: Design Of the Mouse Mog 1-125 Thioredoxin Tag Expression Vectormentioning
confidence: 99%
“…TEV-P recognizes the peptide sequence ENLYFQ↓S/G (27), where Q and S/G correspond to the P1 and P1′ residues, respectively. Even though cleavage sequence mapping studies using peptide combinatorial libraries have shown that the highest stringency was seen for Gln at P1 and that the P2, P4, and P5 positions can be occupied by a number of amino acids, no adventitious cleavage of full-length proteins at sites other than the canonical ENLYFQ↓S motif have been reported (28)(29)(30). We used the YESS system for the directed evolution of a TEV-P mutant library against a library of substrate constructs containing ENLYFX↓S, where X is any amino acid.…”
mentioning
confidence: 99%